New Designs for Graded Refractive Index Antireflection Coatings - MANDJOUB, A.; ZIGHED, L. (Engineering Transactions, 2005)
The constant progress in thin layers technology, especially the graded index inhomogeneous dielectrics, allows the realization of antireflection coatings (ARC) that are less sensitive to thickness and to the incidence angle. Graded refractive index silicon oxynitrides are deposited by Electron Cyclotron Resonance Plasma-Enhanced Chemical Vapour Deposition (ECR-PECVD) controlled in-situ by monochromatic ellipsometry. While avoiding the complexity of the classical multilayer ARCs, the obtained AR coatings permit to obtain the same performances, or furthermore to improve the cells efficiency. Different suggested profiles are optimized by simulation, then they are realized and characterized by spectroscopic ellipsometry and reflectance measurement. The photogenerated current can be enhanced by 45%, and weighted reflectance (between 300 and 1100 nm) reduced to 5.6%. The passivating properties of oxinitrides recommend the use of these AR coatings on texturized surfaces. The weighted reflectance would decrease to less than 1% and short-circuit current will thus be enhanced by 52.79%.